Green Transformational Leadership, Organizational Commitment and Green Human Resource Management on Green Innovation Performance at the Government Sector - Yunita RAHMADANI; Asep Rokhyadi Permana SAPUTRA; Sri Muliati ABDULLAH (Journal of Human Resource Management)
Purpose – The rapid growth of government and business sectors, organizations are always required to create various innovations, especially environmentally friendly innovations, in their human resources. Aims(s) – This study was conducted with the aim of analyzing the influence of global leadership, organizational commitment and environmentally friendly human resource management on environmental management with objectives the government sector, especially the Department of Agriculture, Food and Fisheries of Sleman Regency, Yogyakarta, Indonesia. Design/methodology/approach – This study was conducted with a quantitative approach with a population of 267 respondents and with the Slovin formula with an alpha of 5% obtained 161 sample respondents. The sample method with probability sampling, with quota sampling technique and data collection method with Google form. The analysis used is Structural Equation Modeling (SEM), Convergent Validity, Discriminant Validity, Reliability, Heterojunction Monotrait Ratio (HTMT), Goodness of Fit (GoF) and hypothesis testing, all using SmartPLS software version 4. Findings – The research results prove that green transformational leadership, organizational commitment and green human resource management have a positive and significant effect on green innovation performance. Limitations of the study – The research is devoted to the government sector, subjective measurements of respondents and cross sections, and a 5 point measurement scale. It is hoped that future research can be developed into sectors other than government, measuring using panel data and longitudinal, and measuring more than 5 points. Originality/value – Green innovation research in the government sector is still very rare, considering that this sector prioritizes national culture in its management. This is not a bad thing, in fact this research encourages national culture towards more positive and global changes so that the government is able to compete in the international arena with the collaboration of environmental experts, academics, and research institutions to be of quality in an international standard green environment, so that human resources in government are increasingly environmentally aware, become green leadership, and green commitment.